2017
DOI: 10.1007/s11266-017-9866-9
|View full text |Cite
|
Sign up to set email alerts
|

The Regulation of International NGOS: Assessing the Effectiveness of the INGO Accountability Charter

Abstract: The INGO Accountability Charter is the only global, cross-sectoral regulatory initiative for international NGOs. This is the first independent study of perceptions of its effectiveness, based upon 26 in-depth semi-structured interviews with key individuals from 11 leading international NGOs. Firstly, it analyzes interviewees' beliefs about the motivations of NGOs in joining the Charter. The findings contribute to the scholarly debate about the key drivers for voluntary regulation between 'club theorists' and '… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
46
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
2
2
2

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(51 citation statements)
references
References 16 publications
2
46
0
1
Order By: Relevance
“…Twenty-six in-depth interviews showed that Charter membership provides a defense against actual or anticipated criticism of poor accountability from powerful external stakeholders and also an opportunity for organizational learning. Some members stressed that complying with the Charter's accountability demands is a resource intensive bureaucratic exercise, and expressed their frustration with the low profile of the Charter for donors and staff (Crack 2017). Therefore, the contribution of reducing the accountability gap has not been as effective as wanted.…”
Section: Voluntasmentioning
confidence: 99%
See 4 more Smart Citations
“…Twenty-six in-depth interviews showed that Charter membership provides a defense against actual or anticipated criticism of poor accountability from powerful external stakeholders and also an opportunity for organizational learning. Some members stressed that complying with the Charter's accountability demands is a resource intensive bureaucratic exercise, and expressed their frustration with the low profile of the Charter for donors and staff (Crack 2017). Therefore, the contribution of reducing the accountability gap has not been as effective as wanted.…”
Section: Voluntasmentioning
confidence: 99%
“…SR addresses information asymmetries regarding the organization's impacts on sustainable development and its triple bottom line performance (Hahn and Kühnen 2013). This line of thought is also taken up by club theorists, who discuss the role of voluntary accountability programs as one attempt to mitigate the information problem (Crack 2017;Gugerty 2009). Voluntary information disclosure increases the information basis for the users of SR and allows them to screen the reported content for forming judgment about the triple bottom line performance.…”
Section: Theoretical Discourses Of Sr By Ingosmentioning
confidence: 99%
See 3 more Smart Citations